#### Answer

$-5\frac{1}{3}$

#### Work Step by Step

We plug in the values. We have $(-4)+(-4)\div(3)=-4-4\div3=-4-\frac{4}{3}=-4-1\frac{1}{3}=-5\frac{1}{3}$.

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$-5\frac{1}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.